Teacher Personality Competence in Educating Early Childhood Characters through Jasmine Solusi Playgroups in Cimahi City - Yulianti Fiyul, Arfiani (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2022)
This study aims to analyze the personality competence of teachers in educating early childhood characters. Through play groups. Methods This research uses a qualitative approach by describing what was carried out in the Jasmine Solusi play group in Cimahi City. Data collection techniques through, namely observation, interviews, and documentation studies. Data analysis techniques in this study include Domain, Taxonomy, Componential, and cultural themes. As for checking the validity of the data using triangulation techniques. In conclusion, the teacher's personality competence in forming early childhood character in the Jasmine Solusi Playgroup, Cimahi City. Jasmine Solusi educational staff. Have a personality capable of showing discipline, loyalty, and responsibility. The inhibiting factors causing the teacher's lack of discipline are Jasmine Solutions, which consists of external factors such as the condition of the teacher being very far from the teaching place and vehicles that are not always there. As for the efforts of the principal in improving the competence of the teacher's personality in increasing discipline, loyalty, and teacher responsibility, namely the efforts and leadership of the principal, namely monitoring, and fostering, teacher performance, so that sanctions and rewards will be given to the teacher.